ANALISIS KONSEKUENSI DISPERSI GAS, KEBAKARAN, DAN LEDAKAN PADA TANGKI PENYIMPANAN LPG DENGAN MENGGUNAKAN PERANGKAT LUNAK ALOHA - Maharani, Fandita Tonyka (IDENTIFIKASI, 2020)
This research discusses the analysis of the consequences of gas dispersion, fire, and explosion at SPPBE PT Aroma Jaya Sejati. This study uses a semi-quantitative method that uses secondary company data and direct observation. The data is then analyzed using ALOHA software to determine the extent and impact of gas dispersion, fire, and explosion due to leakage of LPG storage tanks. The results of research in scenario A, scenario A propane dispersion yellow zone reaches a distance of 262 meters, with a propane concentration of 5,500 ppm, the orange zone of propane dispersion scenario A reaches a distance of 133 meters, with a propane concentration of 17,000 ppm. The red zone of propane dispersion reaches a distance of 89 meters, with a propane concentration of 33000 ppm. In scenario B, the yellow zone of propane dispersion reaches a distance of 72 meters with a propane concentration of 5500 ppm, the orange zone reaches a distance of 34 meters with a propane concentration of 17000 ppm, the red zone reaches a distance of 23 meters, with a propane concentration of 33,000 ppm. Meanwhile, jet fire scenario A, for 39 minutes with total burning propane of 46,085 kg with a maximum fuel rate of 3740 kg/minute. The maximum length of the flame reaches 37 meters. Scenario B, a jet fire occurs for 1 hour with total burning propane of 15,088 kg with a maximum fuel rate of 256 kg/minute. The maximum length of the flame reaches 10 meters. Conclusion of propane dispersion in scenario A and B, it is found that the safe distance for propane dispersion is after 262 meters, while the results of jet fire modelling with scenario A and scenario B show that the safe distance for jet fire is after 133 meters.